MANAJEMEN PEMBELAJARAN PKN UNTUK MENINGKATKAN PEMAHAMAN NILAI-NILAI PANCASILA DI SMK - Erni Wijaya (UNIVERSITAS BENGKULU, 2017)
The purpose of this study is to determine whether the management of Civics learning can improve the ability of children's understanding of Pancasila values. This study is a classroom action research. The stages to be carried out in this study include: Planning, Acting, Observing, and Reflecting. This research was conducted in SMKN 2 Kota Bengkulu. The subjects of this study are students of class XII SMKN 2 Kota Bengkulu. Data were collected through observation, diary, comprehension ability test on Pancasila values. Pancasila values that appear in class XII SMKN 2 Bengkulu City is very good, it is proven enthusiastic students in implementing learning Civics in the class, so as to reflect the norms contained in the values of Pancasila is subjective and very universal